The new psychoactive substances 5-(2-aminopropyl)indole (5-IT) and 6-(2-aminopropyl)indole (6-IT) interact with monoamine transporters in brain tissue. (February 2016) - Marusich, Julie A.; Antonazzo, Kateland R.; Blough, Bruce E.; Brandt, Simon D.; Kavanagh, Pierce V.; Partilla, John S.; Baumann, Michael H.
Abstract: In recent years, use of psychoactive synthetic stimulants has grown rapidly. 5-(2-Aminopropyl)indole (5-IT) is a synthetic drug associated with a number of fatalities, that appears to be one of the newest 3, 4-methylenedioxymethamphetamine (MDMA) replacements. Here, the monoamine-releasing properties of 5-IT, its structural isomer 6-(2-aminopropyl)indole (6-IT), and MDMA were compared using in vitro release assays at transporters for dopamine (DAT), norepinephrine (NET), and serotonin (SERT) in rat brain synaptosomes. In vivo pharmacology was assessed by locomotor activity and a functional observational battery (FOB) in mice. 5-IT and 6-IT were potent substrates at DAT, NET, and SERT. In contrast with the non-selective releasing properties of MDMA, 5-IT displayed greater potency for release at DAT over SERT, while 6-IT displayed greater potency for release at SERT over DAT. 5-IT produced locomotor stimulation and typical stimulant effects in the FOB similar to those produced by MDMA. Conversely, 6-IT increased behaviors associated with 5-HT toxicity. 5-IT likely has high abuse potential, which may be somewhat diminished by its slow onset of in vivo effects, whereas 6-IT may have low abuse liability, but enhanced risk for adverse effects. Results indicate that subtle differences in the chemical structure of transporter ligands can have profound effects on biological activity. The potent monoamine-releasing actions of 5-IT, coupled with its known inhibition of MAO A, could underlie its dangerous effects when administered alone, and in combination with other monoaminergic drugs or medications. Consequently, 5-IT and related compounds may pose substantial risk for abuse and serious adverse effects in human users. Highlights: Recreational use of synthetic stimulants has grown rapidly in recent years. Structurally related novel indoles were studied in pharmacological assays. 5-IT and 6-IT were potent substrates at DAT, NET, and SERT. 5-IT produced typical stimulant effects, while 6-IT produced serotonin toxicity. These compounds pose substantial risk for abuse or adverse effects in human users.